The perspective of the young generation towards politics in my locality - Chand, Bibek (Brixton Scholarly Review, 2025)
This project report presents an attitude, belief, and level of engagement related to politics in Bheemdatt Nagarpalika (B.D.N.P)-10, Sukasaal, from the young generation's point of view. For the past ten years, there has been increasing concern over the extent of political engagement among young people, as attitudes and beliefs about politics among them are crucial for the future of governance and civic engagement. The perceptions of the youth from the ongoing political situation will be ascertained, as the interest of the youth in political participation, and what influences their political views. This research design is a mixed-method approach incorporating surveys and interviews to collect information from a sample of young individuals within B.D.N.P-10, Sukasaal. The findings have revealed the complicated relationship of the youth with politics, a combination of engagement and indifference. While many young people are interested in politics, a lot of them are also turned off by the system as it is perceived to have a lot of ills, like corruption, lack of transparency, and many unkept promises. The report continues to discuss the role of social media in shaping the view of political life among the youths and the influence of education on the political awareness of youths. This study brings to the forefront a demand for more inclusive and youth-oriented political strategies to ensure more participation and belief in the system. The insights gained through research will, therefore, help policymakers and political leaders interact with the younger generation and their problems to provide a more active and participatory democratic process within B.D.N.P-10, Sukasaal.